Remote measurement and shape reconstruction of surface-breaking fatigue cracks by laser-line thermography - Qiu, Jinxing; Pei, Cuixiang; Yang, Yang; Wang, Rongbang; Liu, Haochen; Chen, Zhenmao (Elsevier, 2020)
In this paper, a method for remote measurement and shape reconstruction of fatigue cracks by using laser-line thermography (LLT) technique is developed. A new feature parameter derived from the LLT signals is proposed to evaluate the length and estimate the general inner profile of a surface-breaking fatigue crack. An inversion analysis scheme based on conjugate gradient optimization algorithm is then applied to reconstruct the detailed inner profile and dimension of the crack. The reconstruction results with both numerically simulated LLT signals and experimental signals proved the feasibility of proposed inversion scheme and remote LLT method. Based on methods of this paper, not only the size of cracks can be quantitatively evaluated, but the inner profile is also reconstructed for cracks in different shapes from the LLT signals
Keywords: Crack reconstruction; Inverse problem; Quantitative non-destructive evaluation; Fatigue crack; Laser-line thermography